Eucalyptus d'Australie: habitats naturels et dynamique d'evolution - Cossalter, C.; Vigneron, P.; Brooker, M.I.H. (1999)
This paper describes the main ecological and morphological attributes of the eucalypts and related genus Corymbia using Pryor and Johnson's taxonomic classification (1971) and other recent works by Johnson (1976) and Hill and Johnson (1995) as guidelines. The main thrust is on what taxonomy can teach us on 'natural grouping'and 'evolution pathways' within the large and extremely diverse genus Eucalyptus. The description goes from the more primitive forms i.e. the bloodwoods (subgenus Blakella), to those natural groups which are better adapted to new environmental conditions i.e. the subgenus Symphyomyrtus (e.g. section Transversaria) and the stringybarks, blackbutts, ashes and peppermints (section Renantheria) of the Monocalyptus subgenus. Several examples show how the capacity of certain species to survive in a changing environment has been enhanced by the progressive transformation of key morphological attributes. Modern works on the systematics of eucalypts integrate the knowledge on ecology, chemistry, palaeontology, floral biology and genetics in addition to the more conventional studies on morphological traits and their adaptive values. The authors' conclusion is that more attention should be given to taxonomy when the purpose is to explore species' natural variation. Furthermore, it is the authors' opinion that the adaptive capacity of certain Eucalyptus species known for their good performances in plantations could have much to do with the geological history of their natural habitat. This is based on field observations. It seems that the best performing natural populations of several important tropical eucalypts, in terms of adaptation to new environments, are located in mountainous regions affected by the most recent geological events rather than in the geologically unchanged peneplains of northern Australia.